Penguatan Human Resource Syariah untuk Fair and Ethical Recruitment dalam Rantai Pasok Perikanan Global: ABDIMAS Internasional pada Workshop IOM–ILO di Bangkok - Imron Natsir (Universitas Muhammadiyah Manado, 2026)
The global fisheries supply chain remains vulnerable to opaque recruitment, worker-paid fees, unclear contracts, forced-labour risks, and limited access to protection, particularly for migrant fishers. This international community service activity aimed to transform lessons from the Regional Workshop on Strengthening Compliance and Addressing Labour Issues in the Fishing Sector Supply Chain into academic knowledge, teaching materials, and initial recommendations for fair and ethical recruitment from a Sharia Human Resource Management perspective. The activity was implemented through professional participation, knowledge transfer, and structured reflection at Eastin Grand Hotel Sathorn, Bangkok, on 4–5 June 2026. The beneficiaries include lecturers, students, Islamic economics academics, human resource practitioners, employers’ associations, fisheries companies, recruitment agencies, worker organisations, policymakers, and communities concerned with labour migration and worker protection. Data were drawn from the institutional assignment letter, workshop agenda and materials, participatory notes, photographs, panel discussions, official documents, and relevant literature. A reflective-thematic analysis was applied through information reduction, thematic grouping, interpretation, cross-checking, and integration with Sharia principles. The activity produced a labour-issue map, a matrix linking international recruitment standards with amanah, ‘adl, ṣidq, transparency, hifẓ al-nafs, hifẓ al-māl, hifẓ al-‘irḍ, and maslahah, as well as academic dissemination materials and follow-up recommendations. The findings indicate that international labour standards and Sharia ethics share a common orientation toward transparency, prevention of harm, protection of dignity, and sustainable business. The activity contributes a reflective framework rather than statistical generalisation and provides a basis for teaching, research, policy briefs, and future stakeholder engagement.